Atomic layer deposition of high-k and metal thin films for high-performance DRAM capacitors: A brief review - Kim, Se Eun; Sung, Ju Young; Yun, Yewon; Jeon, Byeongjun; Moon, Sang Mo; Lee, Han Bin; Lee, Chae Hyun; Jung, Hae Jun; Lee, Jae Ung; Lee, Sang Woon (Current Applied Physics, 2024)
Dynamic random-access memories (DRAMs) are used as core memories in current computing methods based on the Von Neumann architecture. The DRAM demand continuously increases because of the increased amount of data and need for artificial intelligence computing. DRAM consists of one transistor and one capacitor. Data are stored in the capacitor representing “0” and “1”. DRAM capacitors are composed of metal–insulator–metal thin films. In this review, we summarize experimental methods for development of high-k insulators and metal thin films for DRAM capacitors using the atomic layer deposition (ALD) process. Future research directions for the development of high-k and metal thin films and their ALD processes are addressed for next-generation DRAMs.
Keywords: Atomic-layer deposition; Computing methods; Current computing; Deposition process; Dynamic random access memory; Dynamic random-access memory capacitor; High- k; Metal thin film; Performance dynamics; Thin-films; Atomic layer deposition; DRAM capacitor; High-k; Metal; Thin film